Pelatihan Bahasa Rusia Untuk Meningkatkan Kinerja TNI AD Dalam Bidang Helikopter Seri MI - Susi Machdalena; Anggraeni Purnama Dewi; Nany Ismail (Universitas Serang Raya, 2022)
In the present year, the helicopter MI belongs to ‘Indonesian National Armed Force’ (TNI-AD) is an advanced helicopter produced by Russia. In Indonesia, it is operated not only for guarding the Indonesian’s areas, but also as a shuttle for sending and fetching people from/to the remote areas in the country. Other usage of the helicopter are as the transportation to send the logistic to the remote areas, to evacuate injured people by working-accident or by having an accident in difficult areas. The helicopter is also able to carry, at least, 12 passengers in lying position. This helicopter has many benefits to implement the duty around the remote places of Indonesia, especially the places that are difficult to reach by the ordinary transportation. Since all the guide books are written in Russian language, the officers who are going to operate the helicopter should learn Russian language. While the base Camp of the helicopters are in two places, Jakarta (the capital city) and Semarang (in West Java). Therefore, the language training is conducted in Cimahi, West Java. The participants who learn the Russian language are 12 officers, 2 officers are pilots, another 2 officers are co-pilots, 6 officers mechanics, and 2 other officers are the mechanics for spare-part services. This method uses descriptive method with grammar translation method, oral approach, and lexical approach. The results from the language training are about 8 officers are able to communicate, to write and to read fluency in Russian language, other 2 officers are able but not fluency in talking, writing and reading Russian. Unfortunately, other 2 officers still have difficulties in learning the Russian language.